Echocardiographic diagnosis of primitive ventricle with two atrioventricular valves. Issue 3 (March 1977) - Beardshaw, J A; Gibson, D G; Pearson, M C; Upton, M T; Anderson, R H
Abstract : Anatomical studies have shown that the pathognomonic feature of primitive ventricle is absence of that portion of the interventricular septum which interposes between the atrioventricular valves. The relation of this posterior septum to the atrioventricular valves is such that echocardiography should be a particularly suitable technique for showing its presence or absence. When a posterior septum is present, it is seen on an echocardiogram as a double echo between the two atrioventricular valves. It presence limits posterior movement of the septal cusp of the anterior atrioventricular valve. Absence of the posterior septum should, therefore, be seen echocardiographically as more than mere absence of the double septal echo. It should be possible to show unusual posterior excursion of the "septal" cusp of the anterior atrioventricular valve and apposition of the "septal" cusps of the atrioventricular valves during diastole. In most instances it should also be possible to demonstrate that the posterior great artery is in continuity with both atrioventricular valves. We have shown these echocardiographic features in 26 patients. The diagnosis of primitive ventricle has been confirmed at necropsy or at operation in 4 patients. In the other 22 patients in angiographic data are compatible with a diagnosis of primitive ventricle. Demonstration of these positive features at echocardiography is, therefore, of considerable value in the initial diagnosis of primitive ventricle and in particular its differentiation from other congenital malformations.